2019
DOI: 10.1136/neurintsurg-2019-015237
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy in patients with acute ischemic stroke and ASPECTS ≤6: a meta-analysis

Abstract: BackgroundIt is uncertain whether mechanical thrombectomy (MT) increases the probability of a good outcome (modified Rankin Scale (mRS) 0–2) in patients with Alberta Stroke Program Early CT Score (ASPECTS) 0–6.ObjectiveTo assess the impact of MT in patients with pretreatment ASPECTS 0–6.MethodsAccording to PRISMA guidelines, we performed a systematic search of three databases for series of patients with ASPECTS 0–6 treated by MT. Random-effects meta-analysis was used to pool the following: rate of mRS 0–2 at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 37 publications
(88 reference statements)
7
54
0
Order By: Relevance
“…This may be related to the nursing care of postoperative patients in our hospital and could be improved in the future. Numerous studies have confirmed that age is significantly associated with the prognosis of acute stroke patients (12,21,22). This current study further confirmed the important role of age in the unsatisfactory outcomes and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
“…This may be related to the nursing care of postoperative patients in our hospital and could be improved in the future. Numerous studies have confirmed that age is significantly associated with the prognosis of acute stroke patients (12,21,22). This current study further confirmed the important role of age in the unsatisfactory outcomes and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
“… 22 Another meta-analysis of 17 studies reported mRS score of 0 to 2 for 1378 patients with ASPECTS of 0 to 6; mRS score of 0 to 2 rate was 37.7% for ASPECTS of 6, 33.3% for ASPECTS of 5, 22.1% for ASPECTS of 4, 17.1% for ASPECTS of 0 to 4, and 13.9% for ASPECTS of 0 to 3 groups. 23 These findings, in combination with the present study, suggest patients with low baseline ASPECTS tend to have worse outcomes after MT. A subgroup analysis of a large multicenter retrospective registry (the Bernese-European Registry for Ischemic Stroke Patients Treated Outside Current Guidelines With Neurothrombectomy Devices using the SOLITAIRE FR With the Intention For Thrombectomy [BEYOND-SWIFT]) reported an overall mRS score of 0 to 2 in 24.6% patients with ASPECTS of 0 to 5 at 90 days, with a higher likelihood of favorable outcome (mRS score 0–3) in reperfused patients (Thrombolysis in Cerebral Infarction 2b–3) than nonreperfused (35.2% versus 8.3%, P =0.014), and comparable to those with ASPECTS of 6 to 10 ( P =0.441).…”
Section: Discussionsupporting
confidence: 79%
“…The authors found that even in ASPECTS 4 patients, one in four would be independent, whereas only 14% of patients with ASPECTS 0-3 regained a good functional outcome. 19 In conclusion, there is to date insufficient high-quality evidence to suggest that EVT is both safe and effective in patients with low ASPECTS scores. This was also acknowledged by experts of the European Stroke Organisation, the European Society for Minimally Invasive Neurological Therapy (ESMINT), and the European Society of Neuroradiology in a consensus statement on thrombectomy, 20 leading to the initiation of several randomized controlled trials such as TENSION 21 and RESCUE-Japan LIMIT (ClinicalTrials.gov: NCT03702413).…”
Section: Extent Of Infarctionmentioning
confidence: 92%